The genetics of narcolepsy - Chabas, Dorothee; Taheri, Shahrad; Renier, Corinne; Mignot, Emmanuel (Annual review of genomics and human genetics, 2003)
Human narcolepsy is a genetically complex disorder. Family studies indicate a 20-40 times increased risk of narcolepsy in first-degree relatives and twin studies suggest that nongenetic factors also play a role. The tight association between narcolepsy-cataplexy and the HLA allele DQB1*0602 suggests that narcolepsy has an autoimmune etiology. In recent years, extensive genetic studies in animals, using positional cloning in dogs and gene knockouts in mice, have identified abnormalities in hypothalamic hypocretin (orexin) neurotransmission as key to narcolepsy pathophysiology. Though most patients with narcolepsy-cataplexy are hypocretin deficient, mutations or polymorphisms in hypocretin-related genes are extremely rare. It is anticipated that susceptibility genes that are independent of HLA and impinge on the hypocretin neurotransmitter system are isolated in human narcolepsy.